PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS ANDROID UNTUK MENINGKATKAN PRESTASI BELAJAR GEOGRAFI PADA SISWA KELAS X DI SMA NEGERI 1 PAGAR ALAM - Marweni Marweni (DIADIK, 2021)
This study aims to describe the development of android-based interactive multimedia that was feasible to be developed to improve geography learning achievement and to describe the effectiveness of android-based interactive multimedia that was developed to improve geography learning achievement. This research is included in research and development (Research and Development). The research subjects were students of class in X SMA Negeri 1 Pagar Alam. The data collection technique was done by using assessment sheets and student achievement test. The data analysis used mean and t-test. The conclusion of this research was that android-based interactive multimedia which was developed is feasible to improve geography learning achievement and android-based interactive multimedia which developed was effectively to improve geography learning achievement of tenth grade students at SMA Negeri 1 Pagar Alam